Phenomenological Model of Rubber Bearings With Variable Axial Loading - Domaneschi, Marco; Martinelli, Luca; Cattivelli, Camilla (Frontiers in Built Environment, 2018)
Seismic base isolation systems protect thousands of structures and infrastructures all over the world. Their effectiveness for seismic protection is widely recognized owing to acceleration reduction with a consequent minimization of the structural damage and of the ‘panic’ effect for the occupants. This work deals with the development of a model for simulating the horizontal response of rubber bearings, extending an existent procedure to the case of variable axial loading. A consolidated procedure from literature, demonstrated able to correctly reproduce the complex mechanical behavior of rubber bearing isolation devices under constant axial loading, represents the starting point. Available laboratory cycling tests at variable axial load allow to illustrate the new numerical formulation. An optimization process, based on both automatic and user-driven procedures, is used to identify at different loading conditions the model parameters and the functions to model their variation. The proposed formulation overcomes the limits of the original model in this respect. The developed new version of the bearing model is shown to be capable of simulating with reasonable accuracy the experimentally observed cyclic behavior under coupled vertical-horizontal loading conditions, and the consequences in terms of the device response in the case of a seismic vertical-horizontal concurrent excitations are highlighted.